PENCEGAHAN CYBERBULLYING PADA SISWA MELALUI HEALTH LITERACY PADA SDN 03 ALAI KOTA PADANG - Dewi Murni; Yulastri Arif; Sidaria Ria (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
The use of technology using the internet during online learning has both positive and negative impacts on children. The positive impact of online learning is that it is easy for children to get information via the internet, while one of the negative impacts of using the internet on children is the occurrence of cyberbullying. Cyberbullying occurs when an individual or group uses electronic media and other technology to harm other parties. Several reports from parents of SD N 03 that their children's schools spend more time with electronic media. So that it can cause children to do cyberbullying. To avoid and prevent cyberbullying in children, knowledge dissemination was held with students and class teachers as well as vice principals for student affairs. The process of dissemination of knowledge runs smoothly, students follow closely. Based on the results of the dissemination of knowledge given to students of SD N 03 Alai padang, the average value of students' knowledge and understanding was obtained before the dissemination of knowledge with a mean value = 67.1 while for the results after dissemination of knowledge with a mean value of 69.3. the test results stated that there was an increase in children's understanding of the results of dissemination of knowledge given to students on the topic of cyberbullying. The evaluation results showed that there was an increase in students' understanding and knowledge in cyberbullying. Understanding process is done by pre-posttest. With this activity the school and parents can work together to provide support to children. Optimum monitoring and assistance, to avoid unwanted behaviors.